Impact of foliar diseases and its interaction with nitrogen fertilization and fungicides mixtures on green leaf area dynamics and yield in oat genotypes with different resistance. (July 2019) - Dietz, Juan Ignacio; Schierenbeck, Matías; Simón, María Rosa
Abstract: Crown rust ( Puccinia coronata f. sp. avenae P. Syd & Syd) and leaf spot [ Pyrenophora avenae Ito and Kurib, anamorph Drechslera avenae (Eidam) Sharif] are considered the most important oat fungal diseases in the world, causing high yield and grain quality losses. A major aspect for the management of foliar diseases (mainly crown rust) is the use of host resistant; however most of the oat cultivars available behave as moderately resistant to susceptible. Considering this, fungicides application is a common method of control of fungal diseases in order to reduce yield losses. The objective of this work was to evaluate the effect of foliar diseases and the interaction between N fertilization and fungicides on green leaf area (GLAI), healthy area duration (HAD), grain yield and its components in three oat genotypes; two of them were genotypes obtained by the Breeding Program of the Facultad de Ciencias Agrarias y Forestales (FCAyF), Universidad Nacional de La Plata (UNLP) and a commercial cultivar (Bonaerense INTA Calén). The trials were carried out during two years using a split-split-plot design with three replications. Main plots were two environments: 2011–2014, the sub-plots were the fungicide treatments: with and without fungicide, the sub-sub plots were the fertilization treatments with 0 and 60 kg N.ha −1 and the sub-sub-sub plots were the oat genotypes. Fungicide application decreased the severity percentages at the three growth stages (GS) evaluated during 2014, whereas N fertilization caused increases in the severity of rust, which may be associated with the biotrophic habit of this causal pathogen. However, in the year with high levels of crown rust, N application did not cause effects in GLAI and HAD, due to the effect of N application in increasing the severity of the disease. Fungicide application increased GLAI, HAD and grain yield (GY) with higher responses in the most susceptible genotype (Calén). Results of this study suggest that relating HAD to Grain Yield could be an effective tool in order to improve the quantification and modelling of yield losses under foliar diseases infections. Moreover, the lines belonging to the breeding program of the FCAyF-UNLP showed values of resistance and grain yield superior to the commercial variety evaluated. Highlights: N fertilization increased the severity of oat crown rust. N aggregate did not cause effects on healthy area duration in oat under conducive conditions for crown rust. Fungicide application increased grain yield in susceptible oat genotypes. There was a variable response in grain yield to fungicide applications in resistant oat genotypes.